Identifikasi Lapisan Bawah Permukaan yang Terkontaminasi Lindi Sekitar Sistem Sanitary Landfill di TPA Cahaya Kencana, Kabupaten Banjar - Meirani Agustina; Sri Cahyo Wahyono; Tetti Novalina Manik (Jurnal Fisika FLUX, 2017)
The landfills (TPA) Cahaya Kencana is applying system Sanitary Landfill, the landfill system that is done by the garbage dumped and compacted, then covered with dirt as cover and carried out continuously each end of the operation. This research is very important investigate the distribution of leachate contaminated leachate approximately systems Sanitary Landfill based on the resistivity value and the content of chemical elements in the holding pond. Based on the results of data processing 2D geoelectric Wenner configuration on four tracks with each track length of 100 m were processed using Res2dinv, obtainable at a depth of between 0.75 – 11.6 m resistivity values in the leachate is 4.34 – 10.0 Ωm track 2, 3, and 4, but are not on track 1. The results of laboratory test on four samples consecutive for content. BOD leachate from 26.2 - 121.0 mg/l; and COD 132.5 – 276.2 mg/l is not exceeded the limit of waste water quality standard, except for sample 4 with a COD value of 472.9 mg/l while for pH 7.24 - 7.39 mg/l and the concentration of heavy metals in leachate outlet still on the threshold of normal, where Pb <0.0019 mg/l; Cd <0.0019 mg/l; and Cr <0,0035mg/l.